John of Scythopolis on Divine Darkness: A Neglected Christian Source on Late Antique Jewish Cosmology - Treiger, Alexander (Vigiliae Christianae, 2020)
The present article provides a commentary on the sixth-century Christian bishop John of Scythopolis' scholion on Dionysius the Areopagite's Mystical Theology I.3. In this scholion, John discusses the various Greek translations of Ex. 20:18/21. He also refers to a Jewish cosmological tradition about the seven heavens. Various rabbinic parallels to John of Scythopolis are discussed. The article argues that John most likely has recourse to an oral Jewish tradition, transmitted to him by a Jewish informant in Scythopolis. John of Scythopolis' scholion thus provides important evidence on Christian-Jewish contacts in Byzantine Palestine.